2021
DOI: 10.4193/rhin21.087
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression risk in patients with allergic rhinitis: a systematic review and meta-analysis

Abstract: Background: Allergic diseases appear to be associated with mood disorders. However, particularly regarding allergic rhinitis (AR), such association has not been adequately systematically reviewed. Therefore, we conducted a systematic review and meta-analysis to quantify the association between AR and depression and anxiety. Methodology: We performed an electronic search of PubMed, Web of Science and Scopus for observational studies assessing the association between AR and depression and anxiety. Such associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Allergic rhinitis is associated with mental health problems, such as depression and anxiety. 29 30 31 Like other allergic diseases, allergic rhinitis can also lead to social and interpersonal difficulties and loss of productivity. Subjective worsening of mood with high allergen season has been reported in college students in the United States of America.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis is associated with mental health problems, such as depression and anxiety. 29 30 31 Like other allergic diseases, allergic rhinitis can also lead to social and interpersonal difficulties and loss of productivity. Subjective worsening of mood with high allergen season has been reported in college students in the United States of America.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the proactive use group had a more significantly improved depression score in addition to the overall QOL scale than the as-needed use group. Patients with hay fever were reported to be more likely to have mood disorders such as depression and anxiety [12], and subjective symptoms such as itchy eyes The P values were determined using the Aspin-Welch t test à The P values were determined using the Fisher exact test have been reported to reduce QOL and induce stress and sadness [13]. Proactive use of antihistamine eye drops could be effective in improving QOL during the pollen season by a reduction in the frequency of itching symptoms, and the improvement in QOL could have had an impact on the improvement in mental status.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis found that adolescents with atopic dermatitis took a higher risk of MD in comparison with non-atopic dermatitis (OR = 1.652; 95% CI: 1.463–1.864) ( 24 ). Another systematic evaluation found that AR was associated with MD, and the risk of anxiety and depression in AR patients was higher than that in the non-AR group ( 25 ). Moreover, a systematic evaluation of the association between asthma and anxiety was conducted in 2021 based on observational studies, which found the association between asthma and anxiety disorders (OR = 2.08; 95% CI: 1.70–2.56) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%